2010
DOI: 10.4070/kcj.2010.40.7.334
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab Treatment for Refractory Kawasaki Disease in Korean Children

Abstract: Background and ObjectivesThis was a multicenter study to evaluate the usefulness of the tumor necrosis factor-alpha (TNF-α) blocker infliximab for treatment of Korean pediatric patients with refractory Kawasaki disease (KD).Subjects and MethodsData from 16 patients throughout Korea who were diagnosed with refractory KD and received infliximab were collected retrospectively.ResultsComplete response to therapy with cessation of fever occurred in 13 of 16 patients. C-reactive protein (CRP) concentrations decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
1
31
2
Order By: Relevance
“…28 Since then, infl iximab has been used worldwide for treatment-resistant Kawasaki disease. 7,[29][30][31][32] These anecdotal reports of one to 20 patients all indicated a benefi t with a decrease in clinical signs including fever and markers of infl ammation. An analysis of the Paediatric Health Information System database from 2001 to 2006 showed that 14 of the 27 participating hospitals had administered infl iximab to 48 patients for treatmentresistant Kawasaki disease.…”
Section: Systematic Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…28 Since then, infl iximab has been used worldwide for treatment-resistant Kawasaki disease. 7,[29][30][31][32] These anecdotal reports of one to 20 patients all indicated a benefi t with a decrease in clinical signs including fever and markers of infl ammation. An analysis of the Paediatric Health Information System database from 2001 to 2006 showed that 14 of the 27 participating hospitals had administered infl iximab to 48 patients for treatmentresistant Kawasaki disease.…”
Section: Systematic Reviewmentioning
confidence: 98%
“…We identifi ed several reports worldwide about the use of infl iximab for treatment-resistant Kawasaki disease. 7,[28][29][30][31][32][33] A phase 1 trial of second intravenous immunoglobulin versus infl iximab for intravenous immunoglobulin-resistant Kawasaki disease showed that infl iximab was safe and well tolerated. 8 Subsequently, a retrospective review of intravenous immunoglobulin-resistant patients treated with either a second intravenous immunoglobulin or infl iximab showed that patients treated with infl iximab had fewer days of fever (median 8 vs 10 days, p=0·028) and shorter lengths of hospitalisation (median 5·5 vs 6 days, p=0·04) than those treated with a second intravenous immunoglobulin.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Moreover, some studies reported the increased production of TNFa, and in particular its role in the inflammation of arteries, as immunological marker of acute phase of KD. In fact, infliximab and etanercept, monoclonal antibodies blocking the biological activity of TNF-u, were used for refractory KD patients and were reported to be effective and safe (4,5). An efficient therapy, based on intravenous infusion of high doses of immunoglobulins (lVIG), has been found to effectively reduce the inflammation and the incidence of coronary artery lesions (6).…”
mentioning
confidence: 99%
“…No complications or side effects have occurred in all 15 patients. Table 6 shows a summary of studies that addressed the use of anti TNF-α agents in patients with Kawasaki disease [57][58][59][60][61][62][63]. …”
Section: Kawasaki Diseasementioning
confidence: 99%